Jeffrey fluid flow and heat transfer over a stretching sheet with non-uniform heat source/sink - Ahmad, Kartini; Wahid, Zaharah (INSI Publications, 2015)
This paper presents a steady two-dimensional boundary layer flow and heat transfer of a Jeffrey fluid over a stretched sheet with non-uniform heat source/sink. The governing equations that govern the fluid flow and heat transfer are solved using the Keller-box method after being reduced to a set of non-linear ordinary differential equations by a similarity transformation. The effects of Deborah number β, Eckert number Ec, Prandtl number Pr and non-uniform heat source/sink parameters A*, B* on the flow and heat transfer characteristics are investigated.